Efficacy and safety of traditional Chinese medicine compound DLTM formula on CAC progression in patients with stable CHD: Study protocol for a multicenter, randomized, double-blind, placebo-controlled trial - Qian Xu; Wenting Wang; Xiaochen Wang; Wenwu Liu; Chuyao Qi; Mengmeng Zhu; Jing Cui; Yiwen Li; Yanfei Liu; Yue Liu (Pharmacological Research - Modern Chinese Medicine)
Introduction: Coronary artery calcification (CAC) is closely associated with adverse cardiovascular events in patients with stable coronary heart disease (CHD). Effective treatments specifically targeting CAC progression are still lacking, representing an urgent clinical need. Traditional Chinese medicine (TCM) has been widely used in the prevention and treatment of CHD, playing a crucial synergistic role. This study aims to evaluate the efficacy and safety of DLTM formula in preventing CAC progression in patients with stable CHD. Methods: This multicenter, randomized, double-blind, placebo-controlled trial will be conducted at Xiyuan Hospital of China Academy of Chinese Medical Sciences, the Second Hospital of Anhui Medical University, and Suzhou Hospital of Traditional Chinese Medicine. A total of 194 eligible participants are expected to be recruited. Participants will be randomly assigned to the DLTM formula group and the placebo control group in a 1:1 ratio. All participants will receive a 12-week pharmacological intervention and will be followed up for 9 months after completing the medication. The primary outcome measure is the coronary artery calcium volume score, and the secondary outcome measures include the Agatston score, coronary plaque burden, and the frequency and intensity of angina attacks. Adverse events will be closely monitored throughout the trial. The trial is registered at the International Traditional Medicine Clinical Trial Registry (ITMCTR2024000060). Results: The trial will assess changes in coronary imaging parameters, clinical symptom assessments, and safety profiles, providing objective evidence for the DLTM formula's efficacy and safety. Discussion: This study is expected to fill the clinical treatment gap for CAC, clarify the therapeutic value of the DLTM formula, and offer a novel strategy for managing stable CHD.